PERILAKU KOGNITIF PESERTA DIDIK (STUDI KASUS DALAM MANAJEMEN PEMBELAJARAN) - Alfian Erwinsyah; Ramli Utina; Frida Maryati Yusuf; Erni Muhammad; Muhammad Iksan (LP2M IAIN Sultan Amai Gorontalo, 2022)
This case study aims as a basis or reference for solving students' cognitive-behavioral problems, can have more data to be carried out in the next stage of management, analyze students' cognitive-behavioral problems and align each related element. The case study method used is a qualitative method, with a phenomenon and psychology approach because it involves the cognitive behavior of students in learning management. The method of data collection was done by interview and observation. This case study was carried out by taking 2 students as samples, as well as several teachers at SMP Negeri 3 Limboto. In the data analysis technique, the writer divides the problem identification, analysis, synthesis, diagnosis, prognosis, treatment and follow -up continued. The results of the case study, from the identification of problems these students experienced cognitive-behavioral problems in the form of learning difficulties in learning management. Analysis, students' cognitive problems, namely the difficulty of understanding mathematics, science, and English, lack of willingness to learn, language difficulties, having a shy character, sibling conflict, and verbal bullying experienced students. In synthesis, students lack the motivation to learn, feel lazy to learn, and have a sense of hatred towards a particular subject and conflict. Diagnosis, Internal factors within students and external to their environment. Prognosis, if the problem is not immediately addressed, then what can happen is that no knowledge is transferred and learning achievement will decrease. Treatment, homeroom teachers, and teachers must always cooperate, provide advice to students, and teach slowly until they find comfort in learning. As a follow-up, students can be included in competitions, for example in Sports and the Arts, which are their favorite subjects. Inform parents about problems and treatments that must be carried out as well as those carried out at school.